الآليات القانونية لترقية الموظف العام - -قادري, نجمة; -بوليفة, أسامة (University of Eloued جامعة الوادي, 2022)
تتناول هذه الدراسة موضوع الآليات القانونية لترقية الموظف العام وذلك وفق التشريع الجزائري ، بحيث تعتبر الترقية أهم المواضيع التي تخص الموظف العام والإدارة فهي تمثل الدافع الذي يجعله يلتحق بالوظيفة كذلك الهدف الرئيسي بعد التحاقه إلى جانب الراتب، وذلك بالاعتماد على المنهج التحليلي من خلال تحليل أهم المعايير والمبادئ التي جاءت بها النصوص القانونية والتشريعية الجزائرية. فهي تعني الانتقال من درجة وظيفية معينة إلى درجة أعلى في نفس السلك أو الانتقال من سلك إلى سلك أعلى , هذه العملية تشمل عدة تصرفات قانونية أو ما يسمى بالآليات القانونية تحكمها ضوابط معينة كالطرق التي تتم بها عملية الترقية , وشروط معينة حيث تمر بمراحل أو إجراءات قانونية كي تكون في صورة و وضعية قانونية صحيحة .حيث يتبين أن عملية الترقية تتم بقرار يصدر من السلطة الإدارية المختصة , بعد توفر شروط معينة والتي حددها المشرع سواء تعلقت بالوظيفة أو بالموظف العام , غير أن هذا الحق قد تعترضه موانع تحول دون حصول الموظف على الترقية حتى و إن توفرت فيه الشروط المطلوبة , حيث ينتج عن عملية الترقية حوافز و آثار معينة تأثر في الموظف العام في أداءه والقيام ب عمله خلال مساره المهني , كما أن المشرع الجزائري قد اعترف للموظف العام بحق الطعن ضد الإدارة متى رأى أن قرار الترقية لا يخضع للقانون , وبالتالي وجود وتجسيد الرقابة على قرار الترقية.This study deals with the issue of the legal mechanisms for the promotion of the public employee, in accordance with the Algerian legislation, so that the promotion is considered the most important issues related to the public employee and the administration . During the analysis of the most important standards and principles that came in the legislative and Algerian texts . They mean moving moving from a certain job grade to a higher degree in the same wire or moving from one wire to a higher wire , this process includes several legal actions or the so called legal mechanisms governed by certain controls such as the methods that are it has the promotion process , and certain conditions as it goes through stages or legal procedures in order to be in the form of a correct legal situation , as it turns out that the promotion process is carried out by a decision issued by the competent administrative authority , after certain conditions are met by the legislator , whether related to the job or the public employee , but this the right is obstructed by obstacles that prevent the employee from obtaining a promotion even if he fulfills the required conditions as the promotion process results in certain incentives and effects that effect the public employee in his work during the period . The professional path , and the Algerian legislator has recognized the public servant with the right to appeal against the administration when he deems that the promotion decision is not subject to the law , and therefore there is an embodiment of oversight over the promotion decision .
مذكرة ماستر
Keywords: الموظف العام، الآليات القانونية، ترقية الموظف العام، التشريع الجزائري; public servant , legal mechanisms , public servant promotion , Algerian legislation .